Caracterização de subprodutos do processamento de uvas produzidas no Vale do São Francisco - Ribeiro, Thalita Passos (Universidade Federal Rural do Semi-Árido, 2015)
The by-product recovery of agroindustry can bring opportunities for the development of new products, including food. This potential can be greater when the stuff has different chemical composition, like grapes. For this fruit, an reliable assessment of this potential detailed studies about quality and functional characteristics of the by-product produced during winemaking and processing for juice. Thus, the aim of this study was to characterize the types of by-product generated by processing of different varieties of vine by companies from São Francisco River Valley, to support the agro-industrial use of those recognized with higher levels of chemical compounds and high antioxidant activity. We evaluated titratable acidity, ascorbic acid content, soluble solids content, total soluble sugars content, protein content, pectic compounds content, total extractable polyphenols content, condensed tannins content, anthocyanins content, yellow flavonoids content and antioxidant activity, by the methods of ABTS and DPPH of grapes and by-product (peels and seeds) generated in the winemaking and processing for juice of different varieties. The collected by-product were resulted of the varieties Viognier, Chenin Blanc, Moscato Canelli, Italy, Arinto + Fernão Pires, Tempranillo, Grenache, Mourvèdre, Verdejo and Sauvignon Blanc for processing of white/sparkling wine, and of ‘Tempranillo’, ‘Cabernet Sauvignon’, ‘Syrah’ and ‘Alicante Bouschet’ for processing of red wines. The by-product generated from the processing for juice of the varieties Isabel Precoce, BRS Cora, BRS Violet, BRS Carmen and Bordô also were evaluated. The experimental design was completely randomized, with four replications. Data were separately submitted to analysis of variance according to each processing and the means were compared by Tukey’s test (P <0.05). The peels and seeds by-product, in general, had higher content of ascorbic acid, proteins, polyphenols, anthocyanins, condensed tannins and high antioxidant activity. Thus, the use of by-products of processing of grape may be an alternative to the generation of new food products. However, it is highlighted that the levels were not uniform for the same variety and the same type of processing, requiring differential forms of use of their by-products between companies. The study pointed out that the main by-products processing of different grape varieties that could be used were that one of ‘Syrah’ and ‘Alicante Bouschet’ resulting from the processing of red wines, ‘Tempranillo’, from processing of white/sparkling wine, and ‘BRS Violeta’, the by-products generated in the processing of juices
Keywords: Vitivinicultura tropical; Vinificação; Elaboração de suco; Aproveitamento de subprodutos; Compostos fenólicos; Tropical vitiviniculture; Winemaking; Processing of juice; Use of by-products; Phenolic compounds; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA